Presence of vestibular symptoms and related disability in migraine with and without aura and chronic migraine. (January 2019) - Carvalho, Gabriela F; Vianna-Bell, Flávia Heck; Florencio, Lidiane L; Pinheiro, Carina F; Dach, Fabiola; Bigal, Marcelo E; Bevilaqua-Grossi, Debora
Objective: To assess the presence and handicap due to vestibular symptoms in three subgroups of patients with migraine and controls. Methods: Women between 18–55 years old were diagnosed by headache specialists and stratified as migraine with aura (n = 60), migraine without aura (n = 60), chronic migraine (n = 60) and controls (n = 60). Information regarding demographics, headache and vestibular symptoms were collected in this cross-sectional study. The self-perceived handicap related to vestibular symptoms was assessed through the Dizziness Handicap Inventory questionnaire. Results: A total of 85% of women with migraine with aura and chronic migraine had vestibular symptoms contrasted to 70% of the migraine without aura group ( p  < 0.05), and 12% of the control group reported symptoms ( p  < 0.0001). Patients with migraine exhibited greater Dizziness Handicap Inventory scores than controls ( p  < 0.001); and migraine with aura and chronic migraine groups reached greater scores than migraine without aura ( p  < 0.01). Presence of migraine is associated with a greater risk of vestibular symptoms (migraine without aura: 5.20, migraine with aura: 6.60, chronic migraine:6.20, p  < 0.0003) and with a greater risk of moderate-to-severe handicap (migraine without aura: 20.0, migraine with aura: 40.0, chronic migraine: 40.0, p  < 0.0003). The presence of aura and greater migraine frequency adds to the risk of any handicap (migraine with aura: 1.9, chronic migraine: 1.7, p  < 0.04) and to the risk of moderate-to-severe handicap (migraine with aura: 2.0, chronic migraine: 2.0, p  < 0.0003). Migraine aura, intensity and frequency predict 36% of the dizziness handicap. Conclusion: The prevalence of vestibular symptoms is increased in migraine during and between headache attacks, particularly in migraine with aura and chronic migraine along with an increased handicap due to those symptoms. Vestibular symptoms among subgroups of migraine should be considered when evaluating the functional impact of migraine.